PENGARUH PEMANFAATAN ECENG GONDOK (Eichhornia crassipes) FERMENTASI DALAM RANSUM TERHADAP PERFORMANS ITIK LOKAL JANTAN UMUR 2-9 MINGGU - Siregar, Magdalena; Banjarnahor, Chiristine Octavia (JASA PADI; Vol 5 No 1 (2020): JASA PADI, 2020)
This study aims to determine the effect of fermented water hyacinth (Eichhornia crassipes) fermentation in the ration against the rate of feed consumption, body weight gain, and feed convertion of nine week old male local ducks and to study were determined the best level the rate of feed consumption, body weight gain, and feed convertion of nine weeks. The research design uses a Completely Randomized Design (CRD) with five treatment and each treatment was repeated four times and each repeat consist of five male local ducks. The research showed that water hyacinth (Eichhornia crassipes) fermentation in the ration utilization give unsignificantly (P>0.05) influence to feed consumption and feed convertion. But give significsntly (P<0.05 )to body weight gain.The best level of the giving of water hyacinth (Eichhornia crassipes) fermentation in the ration found on P3 with level15%. ------------------